Biochemical Manifestation of HIV Lipodystrophy Syndrome - Kenneth Ihenetu, PhD; Darius Mason, PharmD (Global Health and Education Projects, Inc., 2012)
Objectives:Highly active anti-retroviral therapy (HAART), including protease inhibitors (PI) have led to dramatic improvements in the quality and quantity of life in patients with acquired immunodeficiency syndrome (AIDS). However, a significant number of AIDS patients on HAART develop characteristic changes in body fat redistribution referred to as lipodystrophy syndrome (LDS). Features of LDS include hypertrophy in the neck fat pad (buffalo hump), increased fat in the abdominal region (protease paunch), gynecomastia and loss of fat in the mid-face and extremities.Methods:The aim of this paper is to review the current knowledge regarding this syndrome. This article reviews the published investigations on biochemical manifestation of HIV lipodystrophy syndrome.Results:It is estimated that approximately 64% of patients treated with PI will experience this syndrome. Biochemically, these patients have increased triglycerides (Trig), total cholesterol (TC), low-density lipoprotein-cholesterol (LDL-C) and extremely low high-density lipoprotein-cholesterol (HDL-C).Conclusions and Public Health Implications:It is hoped that awareness of this syndrome would aid in early diagnosis and better patient management, possibly leading to a lower incidence of cardiovascular complications among these patients.